Preface: 3rd International Conference on Advances in Financial Technology and Economic Management (AFTEM 2024) - Cromwell, Patricia; Liu, Meng (Transactions on Economics, Business and Management Research, 2024)
The 2024 3rd International Conference on Advances in Financial Technology and Economic Management (AFTEM 2024) was held during November 16-17, 2024 in Lyon, France. Aiming at providing an excellent international academic forum for all the researchers and practitioners, the conference enjoys a wide spread participation among all over the universities and research institutes.AFTEM 2024 provides opportunities for the delegates to exchange new ideas and application experiences, establishes business or research relations and global partners for future collaboration. This conference proceeding tends to collect the most up-to-date, comprehensive, and worldwide state-of-art knowledge on financial technology, economic management, business, marketing and other related topics. All the accepted papers have been submitted to strict peer-review by 2-3 expert referees. The conference program is extremely rich, profound, and featuring high-impact presentations of selected papers and additional late-breaking contributions.We sincerely hope that the conference would not only show the participants a broad overview of the latest research results on related fields, but also provide them with a significant platform for academic connection and exchange. We would like to express our sincere gratitude to all the keynote speakers, editors and organizers for their hard work, precious time and endeavor preparing for the conference. Our deepest thanks also go to the volunteers and staffs for their long-hours work. We would like to thank each of the authors and participants for their great contributions to the success of AFTEM 2024.Organizing Committees of AFTEM 2024Lyon, France